Bimbingan Konseling Islam Dalam Meningkatkan Spiritualitas Remaja - Eko Carles (Fokus)
The development of the modern world today, have a significant effect on conduct teens us. Progress in science and engineering is not only give impact positive but also provide negative impact incredibly.Not a little individuals farther away from them. So it needs special attention to tackle negative effects of development the modern world current especially in remaja-remaja us. That smarter to accept the science and technological advances currently, so what passes should been filtered to choose something useful in the process of development of oil to come. Guidance and counseling islam to help develop the ability of individuals.Tries to provide a role in helping in the hope of individuals who guided could be the one who find true happiness and the world.